SIZE DISTRIBUTION, LENGTH-WEIGHT RELATIONSHIP AND SEX RATIO OF HILSA (TENUALOSA ILISHA) IN THE HOOGHLY ESTUARINE SYSTEM - BHAUMIK, UTPAL; SAHA, BISWARUP; SHARMA, ANIL PRAKASH (Journal of the Inland Fisheries Society of India, 2021)
Size distribution, length-weight relationship and sex ratio of Tenualosa ilisha were analyzed from the Hooghly estuary from Frasergunj to Dakshineshwar and from Digha. The length-weight relationship for male, female and both sexes combined were W= 0.0013 L2.57, W= 0.0000038 L3.20 and W= 0.0000064 L3.11 respectively. The predictive sex ratios (Male:Female) at maturity were 52:48 and 38:62 for male and female respectively. There was no effect of male maturity on sex composition, while at female maturity the population was female biased.Key words : Tenualosa ilisha, size frequency, sex ratio, predictive population.